Польский текст в лингвистическом ландшафте восточной части Латвии - Isajeva, Elvira (Studia Rossica Posnaniensia, 2026)
This article examines the characteristics of the Polish text in eastern Latvia, which have evolved over centuries under the influence of changing state borders, political regimes, and sociocultural transformations. The 21st century has brought new challenges and opportunities for the Polish community in Latgale and has influenced perceptions of the local community. Perceptions of the Polish community shape its internal image and identity and are often rooted in persistent narratives that can be reinterpreted in various ways over time. Adding to the significant body of scholarly research on Polish text in Latgale, this article aims to identify the contemporary spheres in which Polish text is presented in the public space of eastern Latvia in the first quarter of the 21st century and to assess its functions in the linguistic landscape of Latgale. The methodology is based on a systemic-functional analysis of Polish text in the Latgale and considers both its verbal and non-verbal forms in the public sphere. The article examples demonstrates the role of historical processes and cultural events in stimulating residents’ interest in regional history and identity, as well as in the formation of Polish text in Latgale. It concludes that Polish text is predominantly present in religious, educational, memorial, social, and cultural spheres, fulfilling specific functions related to the region’s historical and cultural heritage and its contemporary ethno-confessional structure.